Clinical and histological characteristics, and management of melanoma in French Guiana, 2007–2018. (7th June 2020) - Broly, Marine; Drak Alsibai, Kinan; Cenciu, Beatrice; Guevara, Hemerson; Fayette, Jerome; Neidhardt, Eve‐Marie; Demar, Magalie; Couppie, Pierre; Blaizot, Romain
Abstract: There are few studies available on melanoma in Afro‐Caribbean and Amerindian populations of South America. French Guiana deserves a study due to its specific health system and diversity of phototypes. The objectives of this study were to evaluate the incidence, histological and clinical characteristics of melanoma in French Guiana. A retrospective study was conducted from October 2007 to January 2018 on all primary melanomas observed at the Cayenne Hospital Centre. Thirty‐nine patients were included. The incidence rate (1.61/10 6 inhabitants/year) was low compared with mainland France. Median age was 58, and gender ratio 1 : 16. Clear phototype (I/II) patients were the most frequent (38.5%), but a significant amount of melanoma also occurred in darker skin. Median Breslow was higher in dark phototypes than in fair‐skinned patients. Superficial spreading melanoma (SSM) was the most common histological type (33.3%), particularly in patients with clear phototype (61.5%). Acral lentiginous melanoma was found only in darker‐skinned patients (29.1%). The trunk was involved in 66.6% in the clearest group whereas foot was the most common location in the darkest group (60% in V/VI phototypes). Surgery was the most frequently used treatment (79.5%). At the end of the study period, 53.8% had been lost to follow‐up. In conclusion, the incidence of melanoma in French Guiana is lower than in mainland France but remains a public health concern, as dark‐skinned populations often present with advanced diseases. Awareness and prevention in these communities must be improved.